2018
DOI: 10.6001/actamedica.v25i1.3699
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of PRE-DELIRIC (PREdiction of DELIRium in ICu patients) delirium prediction model for the patients in the intensive care unit

Abstract: Introduction.Delirium not only compromises patient care, but is also associated with poorer outcomes: increased duration of mechanical ventilation, higher mortality, and greater long-term cognitive dysfunction. The PRE-DELIRIC model is a tool used to calculate the risk of the development of delirium. The classification of the patients into groups by risk allows efficient initiation of preventive measures. The goal of this study was to validate the PRE-DELIRIC model using the CAM-ICU (The Confusion Assessment M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…In the ICU, the PRE-DELIRIC model 68 , which is based on ten risk factors (age, APACHE-II score, admission group, coma, infection, metabolic acidosis, use of sedatives and morphine, urea concentration and urgent admission) identified within 24 hours of ICU admission, predicted delirium with an area under the receiver operating curve of 0.87 (95% CI 0.85-0.89) in the first 24 hours after admission to the ICU. The PRE-DELIRIC model showed excellent performance in clinical cohorts, including in studies from Lithuania, Scotland and Argentina [69][70][71] .…”
Section: Prediction Modelsmentioning
confidence: 99%
“…In the ICU, the PRE-DELIRIC model 68 , which is based on ten risk factors (age, APACHE-II score, admission group, coma, infection, metabolic acidosis, use of sedatives and morphine, urea concentration and urgent admission) identified within 24 hours of ICU admission, predicted delirium with an area under the receiver operating curve of 0.87 (95% CI 0.85-0.89) in the first 24 hours after admission to the ICU. The PRE-DELIRIC model showed excellent performance in clinical cohorts, including in studies from Lithuania, Scotland and Argentina [69][70][71] .…”
Section: Prediction Modelsmentioning
confidence: 99%
“…Of the 18 included studies, 12 were primarily concerned with the development of new prediction models ( 28 39 ) and six with the validation of existing models ( 20 , 22 , 40 43 ) ( Table 1 ). These studies included 23 risk-prediction models, of which 12 were developed in the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Sample sizes ranged from 94 to 3,284 participants ( 33 , 34 ). Those studies that validated existing models had a sample size ranging from 38 to 2,178 participants ( 42 , 43 ). Delirium was most commonly assessed using CAM-ICU, though several studies used CAM ( 31 ), Nursing Delirium Screening Scale (NuDESC) ( 31 , 39 ), diagnostic and statistical manual of mental disorders (DSM) ( 20 , 36 ), and ICDSC ( 20 , 35 , 42 ).…”
Section: Resultsmentioning
confidence: 99%
“…Delirium is a common neuropsychiatric syndrome in the intensive care unit (ICU) that presents as impaired consciousness, cognition, and attention, [ 1 , 2 ] with a reported incidence that varies from 11% to 87%. [ 3 ] Previous studies indicated that delirium could contribute to prolonged mechanical ventilation duration and ICU length of stay (LOS), as well as a higher mortality rate.…”
Section: Introductionmentioning
confidence: 99%